OECD i „produkcja wiedzy" w systemie globalnego zarządzania - Szymanowski, Rafał (Dom Wydawniczy Elipsa, 2016)
This article aims at analyzing the influence of the Organization for Economic Co-operation and Development (OECD) on the knowledge production in the system of global governance. OECD’s impact on the most important political concepts, social and economic policies and major welfare state reforms in the advanced capitalist countries is analyzed. This article deals in particular with the discourses created by the OECD: transnational growth paradigm, four-speed world, theory of human capital and new public management (NPM). What’s more, the OECD’s data and organization’s impact on welfare state reforms is scrutinized. The author formulates the hypothesis that the OECD creates the most important political concepts, which then provide the theoretical justification for the main directions of public policies and major reforms in the advanced capitalist countries. OECD is an exemplary ‘epistemic community’ that produces certain norms, values and rules of conduct which are later taken and internalized by its member countries. It is not only a useful platform of cooperation on the transnational level, but also a space of socialization to political values, economic ideas and administrative cultures that exist in the rich, developed world.
Keywords: OECD; Organisation for Economic Co-operation and Development; Organizacja Współpracy Gospodarczej i Rozwoju; produkcja wiedzy; globalne zarządzanie; transnarodowy paradygmat wzrostu gospodarczego; wzrost gospodarczy; kapitał ludzki; perspektywa zdolności; nowe zarządzanie publiczne; New Public Management; NPM; państwo dobrobytu; capabilities approach; welfare state; polityki publiczne; public policy; polityka oparta na dowodach; evidence-based policy; globalny kryzys finansowy; kwantyfikacja; podejście ilościowe; think tanki; usługi publiczne